Labour Productivity in the Manufacturing Enterprises of Nepal - Paudyal, Ramjee Prasad (Tribhuvan University Journal, 2010)
The manufacturing public enterprises have now begun to realize the significance of enhancing labour productivity with the emerging environment of competition and liberalization. The ever-growing process of globalization, the open-door policy to imports, and the obvious shift to buyer's market have thrown new demands and challenges on these enterprises. Given these opportunities and challenges provided by the emerging realities, the enterprises have now to match markets with products and other corporate resources more effectively and efficiently to strengthen their competitive advantage. In the current manufacturing environment purchases and personnel expenses (labour) are representing the major proportion of total input. Generally, labour productivity refers to the quantity of output produced by a given quantity of labour input. The labourers are the key determinant of the total value added. More precisely labour productivity is often used as a test of industrial efficiency and even as an index of economic development of a society. Labour productivity is, therefore, fully concerned with the efficient use of labour, so that optimum outputs and benefits could be achieved. Productivity had also suffered because of the failure of the management to adjust to the changes taking place within the workforce. In managing human resources, leadership styles, and motivational systems had not kept abreast of these changes. Furthermore, the negligence to improve and monitor employee productivity and taking corrective actions are evident.